How Service Dogs Enhance Veterans ' Occupational Performance in the Home: A Qualitative Perspective - Terry K. Crowe; Mylinh T. Nguyen; Brenda G. Tryon; Stephanie Barger; Victoria Sánchez (Scholarworks @ WMU, 2018)
Background: This qualitative study explored the lives of veterans diagnosed with posttraumatic stress disorder (PTSD) and/or traumatic brain injury (TBI) and how the partnerships with their service dogs supported improved occupational performance in their homes. Method: Semi-structured individual interviews were conducted with six veterans with PTSD and/or TBI who graduated and received their service dogs from the Paws and Stripes Program in Albuquerque, NM. Home activities of daily living (self-care, household tasks, leisure activities, and family and friend relationships) guided the interview questions. The individual interviews were audio recorded, transcribed, and coded using qualitative data analysis software. Preliminary themes were independently developed by two graduate research assistants. Final themes and subthemes were generated by team consensus. Results: The overarching theme was veteran and service dog partnerships improved occupational performance in the home. Four primary themes arose that supported the overarching theme: (a) providing physical safety and peace of mind; (b) supporting healthy behaviors; (c) my service dog, my hero; and (d) influencing family and friend relationships. Discussion: Findings from this study support that veteran and service dog partnerships improved the veterans' occupational performance in their homes. The service dogs assisted the veterans on physical and emotional levels and improved their healthy behaviors.